Pembuatan Cookies Berbahan Tepung Menir Organik KWT BUMP PT. Pengayom Tani Sejagad - Putri Permatasari; Widiyanto Widiyanto; Amalia Nadifta Ulfa; Indah Nurhidayati; Haryani Saptaningtyas (Jurnal Pengabdian Pada Masyarakat, 2021)
COOKIES FROM ORGANIC GROAT FLOUR TRAINING IN KWT BUMP PT. PENGAYOM TANI SEJAGAD. The rice milling process in addition to producing rice as the main product also other by-products in the form of broken rice or groats, rice bran or husks, and bran or bran. These by-products have not been utilized optimally by the BUMP Pengayom Tani Sejagad which is located in Kebonagung, Sidoharjo District, Wonogiri Regency. This problem is one of the challenges as well as opportunities for training related to groat processing in order to increase the added value of by-products from rice milling. This community service activity aims to provide education and skills to farmers in the Pengayom Tani Sejagad Farmer-Owned Enterprise (BUMP) in processing groats so that they have a higher selling value. The implementation method is the preparation of material handbooks, socialization of processing and innovation of processed food from groats, workshops for processing groats, packaging training, marketing of products from processing groats, and monitoring and evaluation. The service activities carried out can improve the knowledge and skills of target partners in processing, packaging and marketing groat cookies.